ADAPTASI MATA PENCAHARIAN (LIVELIHOOD) DAN WELL-BEING DI PERMUKIMAN KUMUH - Mizan Ikhlasul Rahman (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
Livelihood adaptation analysis provides an understanding of how slum dwellers' activities to cope with the varied constraints and survive in a slum area called Mantuil Village, South Kalimantan, Indonesia. Five capitals, namely human capital, social capital, physical capital, financial capital, and natural capital, are considered in livelihood adaptation analysis. This analysis attempts to fulfill a demand on reducing complex inequality and poverty in the city and to improve inclusiveness in the city and the well-being of slum dwellers. Simultaneously, this research attempts to fulfill a research gap to generate a suggested thorough analysis of the term slum, which considers the existing slum’s characteristics and practices. A field survey is conducted on 164 respondents, to gather information regarding the forms of adaptation experienced by dwellers in Mantuil Village. These forms are classified into five categories of capital. The Rank Based Quotient (RBQ) explores the most influential form of adaptation for improving well-being. The RBQ analysis shows the most influential forms of adaptation for improving well-being are optimizing the current job, intensifying concern for society, buying a motorcycle, expecting financial assistance from family, and utilizing farmland or family-owned land. Eventually, to improve well-being, the most influential forms of adaptation need to be supported and maintained since these are the likeliest forms Mantuil village’s dwellers follow.